Ports 2022. papers from sessions of the 16th triennial international conference, September 18-21, 2022, Honolulu, Hawaii - Erbland, Philip, J.; Jones, Bryan N. (American Society of Civil Engineers, 2022)
This collection contains selected papers from the 16th Triennial International Conference, held in Honolulu, Hawaii. Eighty-four papers are included in this volume on the following topics: simulation and modeling of port operations; berthing, mooring, and bulkheads; rehabilitation and repair of facilities; fender systems; piers and wharves; seismic and storm surge effects; and infrastructure maintenance and upgrades. These papers will be of interest to both practitioners and researchers in the area of port engineering.
"Sponsored by PIANC, Ports and Harbors Committee of the Coasts, Oceans, Ports, and Rivers Institute of the American Society of Civil Engineers."
Keywords: Harbors -- Design and construction -- Congresses.; Structural design -- Congresses.; Harbors -- Environmental aspects -- Congresses.; Hazard mitigation -- Congresses.; Harbors -- Maintenance and repair -- Congresses.; Geotechnical engineering -- Congresses.; elektronické knihy; electronic books